2006
DOI: 10.1016/j.bbrc.2006.09.034
|View full text |Cite
|
Sign up to set email alerts
|

ANP inhibits LPS-induced stimulation of rat microglial cells by suppressing NF-κB and AP-1 activations

Abstract: Atrial natriuretic peptide (ANP) contributes to the inhibition of such causes of inflammation as the lipopolysaccharide (LPS)-induced productions of nitric oxide (NO) and proinflammatory cytokines [including interleukin-1 (IL-1)] in macrophages. In the present study we used primary cultures of rat brain macrophage-like cells (i.e., microglial cells) to investigate whether ANP binding to its receptors inhibits LPS-induced microglial activation via effects on the activation of the proinflammatory transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 22 publications
4
25
1
Order By: Relevance
“…The MAPKs p38, ERK and JNK are known to be activated by LPS, and several studies have demonstrated the significance of MAPKs in the transcriptional regulation of the LPS-induced production of inflammatory mediators via the activation of transcription factor AP-1 [43] . In the present study, we demonstrated that treatment with probucol significantly inhibited LPS-stimulated phosphorylation of p38 and JNK (but not Erk1/2) and the activity of c-Jun, which is a major component of the AP-1 family that is responsible for the over-reactive inflammatory responses of BV2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPKs p38, ERK and JNK are known to be activated by LPS, and several studies have demonstrated the significance of MAPKs in the transcriptional regulation of the LPS-induced production of inflammatory mediators via the activation of transcription factor AP-1 [43] . In the present study, we demonstrated that treatment with probucol significantly inhibited LPS-stimulated phosphorylation of p38 and JNK (but not Erk1/2) and the activity of c-Jun, which is a major component of the AP-1 family that is responsible for the over-reactive inflammatory responses of BV2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, increasing emphasis has been placed on the role of NF-B in the innate immune system. NF-B is the most important transcription factor in inflammatory responses by regulating the expression of various jpet.aspetjournals.org proinflammatory factors such as NO, TNF␣, and IL-1␤ (Jana et al, 2001;Lee et al, 2004;Moynagh, 2005;Moriyama et al, 2006). Nurr1, an orphan nuclear receptor, exerts anti-inflammatory effects by docking to NF-B-p65 on target inflammatory gene promoters, recruiting the CoREST corepressor complex, and subsequently resulting in clearance of NF-Bp65 and transcriptional repression in astrocytes and microglia.…”
Section: Discussionmentioning
confidence: 99%
“…For example, NF-B plays a critical role in the regulation of microglial production of several proinflammatory factors including tumor necrosis factor (TNF)-␣, interleukin (IL)-1␤, cyclooxygenase-2, and nitric oxide (NO) (Jana et al, 2001;Lee et al, 2004;Moriyama et al, 2006;Werner et al, 2008). NF-B activation is detected within the SN of PD patients and a PD animal model created by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) (Hunot et al, 1997;Ghosh et al, 2007).…”
mentioning
confidence: 99%
“…In agreement with this, we have recently reported that ANP, and with less potency CNP, stimulate cGMP formation in ramified microglia co-cultured with astrocytes, as well as in isolated microglia [20]. Furthermore, expression of mRNA for all three NPRs as well as for ANP has been demonstrated in rat microglial cultures [54], suggesting that ANP may be an autocrine regulator in these cells.…”
Section: Expression and Regulation Of The Natriuretic Peptidecgmp Patmentioning
confidence: 59%
“…As in macrophages [71], ANP is not able to induce NOS2 or TNF-a expression in microglia but significantly decreases the induction by LPS of these inflammatory genes [20]. Inhibition by ANP of nitrite accumulation and IL-1b expression has also been described in rat microglial cultures by Moriyama et al [54]. In contrast, enhanced basal and LPS-induced secretion of TNF-a and IL-1b and expression of NOS2 and MHC-II have been reported in rat microglial cells treated for 24 h with zaprinast, an inhibitor of cGMP-selective phosphodiesterases PDE5 and PDE9, or with a high concentration of dibutyryl cGMP (1 mM) [72], conditions that are expected to maintain cGMP levels elevated for longer periods of time than ANP.…”
Section: Actions Of Cgmp In Astroglia and Microgliamentioning
confidence: 71%